Lasers in Forensic Science - Tripathi, R. N. (Himalayan Physics, 2011)
The application of scientific methods of observation and analysis to detect and interpret clues materials at the site of crime as well as analysis of forensic exhibits in the laboratory which include, inter alia, elemental analysis, fl uorescenes of fingerprints, biological stains and other chemicals, particle size analysis, time lapse photography, Raman Laser Probe etc. Key words: Forensic science The Himalayan Physics Vol.1, No.1, May, 2010 Page: 32-33 Uploaded Date: 28 July, 2011